Volatility and the Monetary Approach: Evidence from the Mexican Exchange Market - Lorenzo-Valdés, Arturo; Gallegos-David, Alberto; Trejo-Becerril, Bárbara (International Journal of Economics and Financial Issues, 2025)
This study employs a novel approach by using the GARCH-MIDAS model to estimate the volatility of the nominal exchange rate, incorporating variables of the monetary approach as a long-run component. We analyze the daily closing prices of the peso-dollar nominal exchange rate from July 1991 to December 2022 and the quarterly macroeconomic fundamentals from September 1988 to December 2022. Our findings reveal a significant influence of the monetary approach variables on the long-term feature of the exchange rate volatility. We find that the bias of long-term volatility is contingent upon the distinctive functional relationship fundamental to the demand for real money balances. Our investigation concludes that the specification grounded in the monetary approach yields more robust volatility predictions when compared with alternative models.